Budowanie komunii z Bogiem w rodzinie przez słowo Boże - Wiszowaty, Edward (Studia Pastoralne, 2026)
Marriage and the family are today the subject of many studies in the area of humanities, to mention the social anthropology, pedagogy, psychology, sociology, including the sciences of theology. On the one hand studies draw attention to the significant changes that have taken place in the space of the functions of these institutions, on the other hand to the secularization of marriage and family and the ensuing crisis, the most glaring example of which is the growing number of divorces. At the same time longing for a successful marriage and family relationships as the source of a happy life seems to be un undeniable fact. The author of the article in the article, in the submitted analyses, seeks to show that true community can exist only on the foundation of the word of God. At the same time he shows the practical dimension of life with the word of God in the family. He draws attention to reading and meditating on the word of God and the role of the word in building relationships, resolving of family crises and upbringing children.